HIV Pediatric Care Quality in Togo's Health Facilities in 2014 - Azoumah, K. D.; Agbéko, F.; Djadou, K. E.; Segbedji, K. A. R.; Géraldo, A.; Takassi, O. E.; Douaguibe, B.; Agbèrè, A. D.; Atakouma, Y. D. (Journal of Child Science, 2018)
In 2013, children living with human immunodeficiency virus (HIV)(CLHIV) and on antiretroviral therapy (ART) in Togo accounted for 7.6% of people living with HIV on ART. Management faces many challenges due to insufficient qualified human resources. This study aimed to assess the availability of care offered to these children in health facilities. This was a retrospective descriptive study on 244 CLHIV (under 15 years) who were on ART and randomly selected in 26 sites providing HIV medical care in Togo from July 22 to September 06 2014. Evaluation forms on children's clinical, biological, and therapeutic parameters were analyzed. Forty percent of CLHIV were between the ages of 5 and 9 years. The average age was 5 years at testing for diagnosis; 49% of children were in the World Health Organization (WHO) stage III–IV. The sex ratio (male/female [M/F]) was 1:1. Almost 71% of CLHIV were underweight (weight-for-age <  − 2 Z scores Severely underweight : weight-for-age  <  −  3 Z scores). The patient height was not recorded in 81.6% of the cases. According to the guidelines, the criteria to be on ART were met for 90.2% of children. The average delay (from diagnosis) to be on ART was 216 days. First-line regimens were mostly zidovudine/lamivudine/nevirapine (AZT/3TC/NVP) (47.0%) and stavudine/lamivudine/nevirapine (d4T/3TC/NVP) (38.7%). Follow-up was characterized by a low rate of achievement of the biological semi-annual evaluation (19.8%), child compliance for 62.7%, a cotrimoxazole prophylaxis for 70.2%, and tuberculosis screening for 64.8%. The lost-to-follow-up (LFU) proportion was 8.9%. HIV pediatric diagnosis is still an issue in Togo. Early maternal and child healthcare and HIV care are not optimal. Recruitment and capacity building of health professionals, delegation of tasks to paramedics, and innovative motivation processes could improve care for HIV-infected children.
Keywords: HIV; children; care; Togo